SIFAT KIMIA TANAH PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI SEKITAR TAMAN NASIONAL LORE LINDU (STUDI KASUS DESA TORO KECAMATAN KULAWI KABUPATEN SIGI SULAWESI TENGAH) - Azmul, Azmul; Yusran, Yusran; Irmasari, Irmasari (Jurnal Warta Rimba, 2016)
Over the function of land can affect soil condition that involve either chemical, physical or  biological characteristic of it. Soil chemical component that affected by : soil pH, C-organic, N, P, K and Cation Exchange Capacity. Toro village in Sigi Subdistrict is a village nearby Lore Lindu National Park that has different types of  land use. The research aimed to find out the soil chemical characteristic in various types of land uses around Toro village, Kulawi subdistrict, Sigi District, Central Sulawesi. The research was conducted on May up to the month of July 2015, on three types of land uses were primer forest (Wana Ngkiki), secondary forest (Pangale) and agroforestry land  (Oma) around Lore Lindu National Park, Toro village, Kulawi subdistrict, Sigi district, Central Sulawesi. The research started by doing  field survey, deciding sample swath spot, taking soil sample, analyzing soil sample in laboratorium. Deciding spot of taking soil sample was done purposively (purposive sampling) which done in the depth of  ≤ 30 cm. The result of the research showed that the soil chemical characteristic of various types of land uses was varies. Soil in primer forest (Wana Ngkiki) had chemical chracteristic as follows: pH (H2O) that tended to be acid 5.05, C-organic 3,56 %, N-total 0,63 %, T- available (Bray I) 1,49 ppm, K-total 0,96 mg/100g and CEC 28,83 cmol (+) kg-1. Soil chemical characteristic of secondary forest (Pangale) was pH (H2O) 4.78, C-organic 1.54 %, N-total 0.49 %, P-vailable (Bray I) 4.97 ppm, K-total 4.57 mg/100g dan CEC 8,46 cmol (+) kg-1. The soil chemical characteristic of  agroforestry land (Oma) was pH (H2O) 5.05, C-organic 1.39 %, N-total 0.13 %, P-available (Bray I) 5.35 ppm, K-total 3.73 mg/100g and CEC 8.93 cmol (+) kg-1.Keywords : Soil Chemical Characteristic, Land Use,  Lore Lindu National Park